MODELING AND DYNAMICS OF PUZZLING SPACE PROBES ANOMALIES IN SPACE ENGINEERING - Rai, Ankush; R, Jagadeesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
The anomalous delay of Pioneer 10, the unexpected increase of velocity & radius of space probes & celestial bodies is discussed respectively. An attempt is made to solve this puzzling anomaly. Deprived from empirical properties of nuclear matter an inverted potential in an anisotropic pressure is added to the space which avail us to account for the explanation of this anomalies. Â  Â 